2016
DOI: 10.14191/atmos.2016.26.2.289
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Aerosols Related to Haze Events over Seoul Inferred from Skyradiometer and Satellite-Borne Measurements

Abstract: Optical properties of aerosols associated with haze events over Seoul were examined using ground-based skyradiometer and satellite-borne CALIOP and MODIS measurements over the 2009~2010 period. It is shown that aerosol optical thickness (AOT), Ångström exponents (α), and fine-mode particles increase during the haze events. The CALIOP-measured vertical profiles of aerosol during the haze events revealed that most of aerosols are loaded within layers below 4 km altitude. A large portion of these events appear to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Therefore, it is expected that Korea reveals the AOD east-west gradient if the prevailing winds are westerly and the airmass originates in or passes through the polluted area during the observation. As discussed earlier, [27] showed that the airmass that caused high aerosol concentrations in Korea originated from the northern and southern parts of China (Beijing and Shanghai). Here, Beijing and Shanghai are to the west or southwest of Korea, capable of efficiently transporting aerosols to the Korean Peninsula through the westerly winds.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Therefore, it is expected that Korea reveals the AOD east-west gradient if the prevailing winds are westerly and the airmass originates in or passes through the polluted area during the observation. As discussed earlier, [27] showed that the airmass that caused high aerosol concentrations in Korea originated from the northern and southern parts of China (Beijing and Shanghai). Here, Beijing and Shanghai are to the west or southwest of Korea, capable of efficiently transporting aerosols to the Korean Peninsula through the westerly winds.…”
Section: Discussionmentioning
confidence: 80%
“…The effect of aerosol origin and path on the PSD shape and the maximum size is discussed in Section 4. Previously, [27] analyzed the airmass origin associated with haze events in Seoul from 2009 to 2010. They showed that the high concentrations of aerosols observed over the Korean Peninsula were linked to the airmass originating from highly populated polluted areas (northern and southern China, such as Beijing and Shanghai) and transported to Korea through the westerly.…”
Section: Particle Size Distributionmentioning
confidence: 99%